2013
DOI: 10.4236/health.2013.511258
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of health professionals’ attrition from public health sectors in Bahir Dar City, Ethiopia

Abstract: Background: Attrition of health professionals from public health sectors is found to be a barrier to effectiveness of health systems and to provide essential health service to population. In Ethiopia, the public health system is the major provider of health care service to the people. In particular, the poor segment of community uses public hospital, health centers and clinic, since the private health facilities are inaccessible and unaffordable to them. The aim of this study was to determine the magnitude and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This may be because more senior and qualified health workers had transferred from rural to urban facilities. Staff transfer is a common practice in the health system to reduce staff attrition rate [ 45 ]. This imbalance created different achievement levels in reaching the information revolution targets in all districts, which, in turn, can affect the quality of care provided to beneficiaries in general.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because more senior and qualified health workers had transferred from rural to urban facilities. Staff transfer is a common practice in the health system to reduce staff attrition rate [ 45 ]. This imbalance created different achievement levels in reaching the information revolution targets in all districts, which, in turn, can affect the quality of care provided to beneficiaries in general.…”
Section: Discussionmentioning
confidence: 99%
“…There were 133 physicians in the region in 2005 and number drastically dropped to 68 in 2006 [28]. A survey study in the public health centers at Bahir Dar unveiled that the attrition rate of health professionals is 39.6% [30]. In addition, a study conducted among nurses in referral hospitals of the Amhara regional indicated that 60.2% of participants reported intention to leave their job [31].…”
Section: Introductionmentioning
confidence: 99%